Phenomena of Malaysian, and Japanese Languages from an Intercultural Communication Perspective - Machawan Arsyl Elensyah Rhema; Sanjaya Sonda; Zubbir Nadiah Binti (SHS Web of Conferences)
This research focuses on field findings related to the phenomena of Malaysian, and Japanese languages from an intercultural communication perspective, encompassing language phenomena in written and spoken forms. Additionally, the research aims to understand the dynamics of interpersonal communication interactions across cultures as experienced firsthand. Employing a qualitative method, supplemented with an ethnographic approach tailored to how researchers gather data, this study examined Japanese language phenomena and language phenomena used in the Malayan Peninsula region (Singapore and Malaysia) over five days. The research findings, which have practical implications, indicate that while Indonesian and Malaysian languages share the same Latin-based writing system, there are vocabulary differences that can confuse users of both languages. In oral contexts, misunderstandings of certain expressions that can lead to miscommunication occur, despite the shared characteristics between Indonesians and Malaysians. On the other hand, the Japanese written language reflects the population of Japanese residing in regions using the Japanese script. Japanese language phenomena in spoken form reveal the use of mixed English and Japanese, informal language when meeting new people, and discussions related to privacy during initial introductions.